(untitled) (Research, Society and Development, 2022)
Bacterial resistance is one of the biggest global health challenges, impacting around 700.000 deaths per year, in addition to dramatic consequences in the hospital and social spheres. Although it is a growing and highly threatening problem, the number of effective drugs available to combat these superbugs is increasingly limited, making the importance of the search for new options for antibiotic therapy emphatic. This study aimed to produce silver nanoparticles stabilized in hydroalcoholic extract of mastruz; to characterize them through of Visible Ultraviolet (UV- Vis); evaluate the stability of silver nanoparticles after 48h and 72h; characterize the hydroalcoholic extract of mastruz through spectrophotometric study and analyze the bactericidal potential of silver nanoparticles. Silver nanoparticles were developed through green synthesis, later characterized by Spectrophotometric Visible Ultraviolet (UV- Vis) and applied to cultures of Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa e Klebsiella pneumoniae) and Gram positive (Staphylococcus aureus). The nanoparticles were produced through green synthesis, showed a maximum absorption peak of 400 nm in the spectrophotometric study, and they remained stable after 48h and 72h. The hydroalcoholic extract of mastruz showed two peaks of maximum absorption (332 nm and 674 nm) in the spectrophotometric analysis. Also, the bactericidal activity of the silver nanoparticles was observed, through the presence of inhibition halos of approximately 14 mm in the tested cultures.